2015
DOI: 10.1038/srep14526
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual temporal recalibration occurs independently at two different time scales

Abstract: Combining signals across the senses improves precision and speed of perception, although this multisensory benefit declines for asynchronous signals. Multisensory events may produce synchronized stimuli at source but asynchronies inevitably arise due to distance, intensity, attention and neural latencies. Temporal recalibration is an adaptive phenomenon that serves to perceptually realign physically asynchronous signals. Recently, it was discovered that temporal recalibration occurs far more rapidly than previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 36 publications
5
66
0
Order By: Relevance
“…The results are plotted in Figure 5 and show very clearly that temporal recalibration arising from inter-trial adaptation is strikingly consistent throughout the test period. This was shown recently for inter-trial recalibration to AV asynchrony (Van der Burg, Alais, et al., 2015). Here, we replicate that effect for AV stimuli and extend it to AT inter-trial recalibration.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The results are plotted in Figure 5 and show very clearly that temporal recalibration arising from inter-trial adaptation is strikingly consistent throughout the test period. This was shown recently for inter-trial recalibration to AV asynchrony (Van der Burg, Alais, et al., 2015). Here, we replicate that effect for AV stimuli and extend it to AT inter-trial recalibration.…”
Section: Resultssupporting
confidence: 75%
“…Figures 4 and 5). For the AV combination, both the recalibration magnitude and its sustained pattern are consistent with our earlier reports conducted with non-collocated stimuli (Van der Burg et al., 2013; Van der Burg, Alais, et al., 2015). The current results complement those earlier reports in showing that the effect also occurs when stimuli are collocated, establishing that inter-trial recalibration for AV stimuli occurs without spatial selectivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While passive exposure to asynchronous stimuli has been previously observed to alter the perceptual representation of perceived synchrony, both over the course of many trials (Fujisaki et al 2004; Vroomen et al 2004; Van der Burg et al 2015a) and trial-to-trial (Van der Burg et al 2013; Van der Burg et al 2015b), passive exposure to asynchronous does not seem to enhance temporal acuity. Although these prior studies, along with those studies that observe enhancement of temporal acuity with feedback (Powers et al 2009), suggest that a reinforcement signal was needed to enhance multisensory temporal acuity, the properties of the stimuli employed during perceptual training have not been systematically explored (Powers et al 2009).…”
Section: Discussionmentioning
confidence: 86%
“…While it is difficult to determine that no change in criterion occurs following perceptual training, recently, it has been suggested that prolonged changes in the calibration of multisensory temporal representations may be elicited primarily from changes in criterion at the higher-order decisional level whereas as transient trial-to-trial changes in multisensory temporal representations (i.e. rapid recalibration) result from changes at low-level sensory processes (Van der Burg et al 2015a). Furthermore, changes at decisional stages of perception have been recognized to contribute to other forms of perceptual learning (Law and Gold 2008; Law and Gold 2010).…”
Section: Discussionmentioning
confidence: 99%